Accelerated Aging Process of Bio-Oil Model Compounds: A Mechanism Study - Wang, Rui; Ben, Haoxi (Frontiers in Energy Research, 2020)
Bio-oil, obtained from the pyrolysis of biomass, is identified as a potential material for producing transportation fuels and value-added chemicals. However, the physical and chemical properties of bio-oil change with time, known as “aging,” and the instability of bio-oil brings a critical hurdle to the commercial application of bio-oil. Therefore, expanding and deepening the understanding of the aging mechanism of bio-oil is the key to later efficient application of bio-oil. In addition, the extreme complexity of pyrolysis bio-oil composition brings great difficulties in studying the aging mechanism. Thus, this study tries to better understand the aging mechanism by evaluating the aging performance for 39 model compound aging tests performed at 80°C for 72 h. Four kinds of reactions (self-condensation, esterification, aldol condensation, and phenol, and aldehyde reaction) were investigated to understand the contribution of various compounds and reactions during the aging process. It has been found that acids played an important role in the aging process, as these acted as the reactant in the esterification reaction and acted as the catalyst for aldol condensation and phenol and aldehyde reaction. Acids and alcohols reacted via the esterification reaction, resulting in the decline of aliphatic C-O bonds. Due to the absence of acids, aromatic compounds were relatively stable in these tests. In comparison, aldehydes and HMF were active since self-condensation reactions for these chemicals were observed in the absence of acids. Moreover, with the aid of acids, HMF showed high tendency toward polymerization during the accelerated aging process.